Elementary set theory, parts I and II - Leung, Kam-tim (Hong Kong University Press, 1967)
This book provides students of mathematics with the minimum amount of knowledge in logic and set theory needed for a profitable continuation of their studies. There is a chapter on statement calculus, followed by eight chapters on set theory.